Islamic Law for Business and its Legal Bases in Indonesia - Muhlis; Muhammad Fazlurrahman Syarif (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
Islamic law has a crucial position and meaning in the context of implementing human development, just like in business in Indonesia. Thus, this study demonstrates Islamic law's perspective in business. This research uses a library approach which can be in the form of the Qur'an, Hadith, scientific works, research reports, scientific journal articles, laws and regulations, and official website sources. The study results reveal that Islam descends as a comprehensive religion, so its teachings do not have a partition only on the rituals of worship of mahdah and ghairu mahdah but including activities of human life with respect to economics. Therefore, there is a need for sharia principles in business practice and implementation because it provides hope and development so that sharia-compliant business law offers solutions for everyone. The sources of Islamic law are the Qur'an and the Sunnah of the Prophet, and then if no instructions are found and the method of ijtihad can be used as a guide. This has been implemented in the laws and regulations.